Optimizing investments' cash flow: a scheduling approach. (2003)
In this paper, the problem of optimising cash flow so as to enhance the financial feasibility of a multipart project is considered. The problem has been modelled as a single machine scheduling problem. Several sectors of the Nigerian economy where this problem is encountered are also discussed. A real life problem was solved on a PC using an electronic spreadsheet.